SUBSEQUENT EVENTS AND THEIR IMPORTANCE IN DRAWING UP ANNUAL FINANCIAL STATEMENTS - Daniel Botez (Studies and Scientific Researches: Economics Edition, 2014)
Subsequent events, called so because they are recorded after the closing date of financial year, must be recorded and taken into account in drawing up the financial statements. Some of them can fundamentally changing financial position of the entity or provide information to users absolutely necessary for their decisions. Accounting treatment in this situation is provided for by International Standard of Accounting ISA 10 “Events after the Reporting Period”, whose provisions are taken to a large extent in national accounting standards. For financial auditor, investigating how the subsequent events are presented in the financial statements shall constitute a procedural obligation. Auditor`s procedure is based on the provisions of an specific International Standard on Auditing, ISA 560 “Subsequent events”. He shall be required to satisfy itself that in the financial statements shall be presented all treatment and appropriate information concerning subsequent events.